A comprehensive review on vibration based micro power generators using electromagnetic and piezoelectric transducer mechanisms. (December 2015) - Siddique, Abu Raihan Mohammad; Mahmud, Shohel; Heyst, Bill Van
Highlights: A comprehensive survey of electromagnetic and piezoelectric MPGs is presented. This paper will help to develop a new configuration of EMPG and PMPG in future. This paper will help to identify the application fields of different MPGs. This paper will allow developing hybrid MPGs with optimum output. Abstract: The area of micro power generation has developed significantly over the last two decades in the field of microelectromechanical systems, self-powered wireless sensor nodes, and mobile platforms. Battery is the main power source of such systems but it has some limitations which include finite life time, periodic replacement, and environmental pollutions. Therefore, electrochemical battery system is not a suitable fit for wireless self-powered electronic industry. Energy harvesting through renewable energy such as mechanical vibration can be an attractive alternative solution to replace or widen the lifespan of the traditional battery system. A good number of researches have been conducted on vibration based micro power generation to support the microelectromechanical systems. Electromagnetic, piezoelectric, and electrostatic transducers are used to convert kinetic energy (i.e., mechanical vibration) into electrical energy. A comprehensive literature review has been presented on vibration based micro power generation using two most common transducer mechanisms: electromagnetic and piezoelectric transduction systems.